Pengaruh Terapi Akupunktur Jin’s 3 Needle Terhadap Penurunan Skala Nyeri Pada Pasien Nyeri Lutut Di Dusun Sidorejo Desa Ngargorejo Kecamatan Ngemplak Boyolali - Joko Tri Haryanto; Yuwinda Ginung Pradina; Estuningsih Estuningsih (Jurnal Keterapian Fisik, 2017)
Abstract:Acupuncture Jin's 3 Needle for knee pain. Knee pain is a disorder of the musculoskeletal system include the patella bone, knee joints, and soft tissue (blood vessels, nerves, ligaments, muscles, and tendons). Knee pain is a painful disease that is often complained of by parents, adults, and children. In general, knee pain can occur immediately after trauma and may be due to degenerative factors or conditions caused by osteoarthritis, rheumatoid arthritis, and gout. According to the World Health Organization (WHO) in 2008,it is known that knee pain suffered by 151 million people around the world who occupy the sixth position causes mild motion obstacles to heavy movement obstacles. Therefore knee pain needs to get special treatment to overcome the complaints of pain. One of the handling quite effective to lower the pain scale is to use acupuncture therapy. This research is research pre-experimental design One-Group Pretest-Posttest Design with a sample of 17 residents of the village Ngargorejo village of Sidorejo Subdistrict Ngemplak Boyolali which meet the criteria of inclusion. Statistical tests using univariate analysis and bivariate analysis. In bivariate analysis use the wilcoxon test. Research results acupuncture therapy Jin's 3 Needle affects the decrease of pain scale in knee pain patients with p-value statistic test result 0,000 (p < 0,05) where H0 is rejected and Ha accepted.